Meningkatkan Kemampuan Mengenal Huruf Braille Melalui Media Kartu Huruf Anak Tunanetra - Rani Satria (Universitas Negeri Padang, 2012)
Against the background of this research with the problems that researchers found in SDLB N 35 Painan, class of blind children DI / Half blind children who have problems is very low ability to recognize braille. Under these conditions, the researchers want to try to establish if the media card letter can enhance the ability of blind children in improving abilitym to know the wide range in the class I SDLB N 35 Painan. This study used an experimental approach in the form of single-subject research (the study of a single subject), the AB design and data analysis techniques using visual analysis chart. The subjects were blind children. Based on the results of this study indicate that the ability of children to recognize the wide range can be increased through the medium of letter cards. Performed at baseline conditions in the seven observations of the child's ability to recognize the same range as 13% -30%, the condition of interventions improve children's ability to recognize the child as much as 36% range -93% correct. Thus the hypothesis is accepted by the trend (+), the tendency of variables and data stability overlape 0%, which means that through the media card can enhance the character of children in SDLB N 35 Painan. Related to the results of research in improving the ability to know braille for blind children X increases, the researchers suggest the teacher to use the media card to improve the ability to determine blind child kedepanya wide.